The advertisement call of the Cape Melville Treefrog Litoria andiirrmalin (Anura: Hylidae) - Hoskin, Conrad J. (Zootaxa, 2014)
The Cape Melville Treefrog, Litoria andiirrmalin McDonald 1997, is a hylid frog restricted to granite boulder fields and associated rainforest of the Melville Range on Cape Melville, north-eastern Australia. The species has remained poorly known because the Melville Range is rugged and remote, with limited accessibility during the summer wet season when frog activity is generally greatest. Litoria andiirrmalin is a large frog that inhabits boulder-pile habitat in the vicinity of streams. The original description had little information on breeding biology. The tadpole was not known at that time but has been described recently (Meyer et al. 2013). The call was not recorded but was described as “a rapid, gentle toc toc toc toc toc” (McDonald 1997).